2007
DOI: 10.1016/j.euje.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler echocardiography reliably reflects severity of iron overload in pediatric patients with β thalassemia

Abstract: Decreased DT, increased PVAR-MVA duration, and increased E/Em ratio reliably reflected severe iron overload in pediatric patients with beta thalassemia. Systolic and diastolic LV function is preserved in patients who have serum ferritin <2500 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…β-TM patients with mean serum ferritin ≥2500 µg/l had significantly lower EF and higher TRV than those with serum ferritin <2500 µg/l ( Table 2). In agreement with our findings, Silvilairat et al [27] reported a preserved systolic and diastolic LV function in patients who have serum ferritin <2500 ng/ml. Hamdy and colleagues [55] showed that the presence of right ventricle systolic dysfunction in patients with β-TM is related to high levels of serum ferritin.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…β-TM patients with mean serum ferritin ≥2500 µg/l had significantly lower EF and higher TRV than those with serum ferritin <2500 µg/l ( Table 2). In agreement with our findings, Silvilairat et al [27] reported a preserved systolic and diastolic LV function in patients who have serum ferritin <2500 ng/ml. Hamdy and colleagues [55] showed that the presence of right ventricle systolic dysfunction in patients with β-TM is related to high levels of serum ferritin.…”
Section: Discussionsupporting
confidence: 82%
“…According to the literature, the cutoff value 2500 µg/l was used to classify patients into two groups as it was defined to be the best for prediction of thalassemia complication [26] and has been used for prognosis with higher incidence of cardiac complication and shortened survival in patients with levels >2500 µg/l compared with lower levels [27,28].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…In literature, we found few studies conducted in beta thalassemia patients which can be compared with our study (18)(19)(20)(21)(22). Specifically, tissue Doppler examination in the study performed by Vogel et al (18) included segmentary measurements as in our study.…”
Section: In 2001mentioning
confidence: 91%
“…When conventional findings of heart failure are observed on echocardiography, the prognosis of cardiomyopathy is frequently fatal (17). Recently, introduction of tissue Doppler for evaluation of diastolic function indicates that significant advances will be made in terms of early diagnosis of cardiomyopathy in patients with thalassemia major (18)(19)(20)(21)(22). In additon, usage of T2-star imaging method showing cardiac iron load has been the most important development for early diagnosis of risk of heart-related complications in recent years (23).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Parale et al evaluating diastolic cardiac functions in pediatric thalassaemia patients documented that E/Em ratio exhibited statistically signi cant elevation in the thalassaemia group [15]. A study by Silvilairat et al evaluating severity of iron deposition by tissue Doppler imaging in a pediatric patient population showed that E/Em ratio was calculated to be signi cantly elevated in the patients with mean ferritin level > 5000 ng/ml, whereas the amplitude of Sm wave was signi cantly decreased in the patients with ferritin level greater than 2500 ng/ml [16]. We identi ed in accordance with the previous studies that E/Em ratio showed statistically signi cance increase in the thalassaemia group compared with the control group in addition to Em ve Sm waves of statistically signi cant lower amplitude.…”
Section: Discussionmentioning
confidence: 99%